2017
DOI: 10.3390/ijms18061291
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Polyplex Formation between DNA Oligonucleotide and Poly(ʟ-Lysine): Experimental Study and Modeling Approach

Abstract: The polyplexes formed by nucleic acids and polycations have received a great attention owing to their potential application in gene therapy. In our study, we report experimental results and modeling outcomes regarding the optimization of polyplex formation between the double-stranded DNA (dsDNA) and poly(l-Lysine) (PLL). The quantification of the binding efficiency during polyplex formation was performed by processing of the images captured from the gel electrophoresis assays. The design of experiments (DoE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…As previously discussed, NMR showed that histidines/imidazoles formed hydrogen bonds with nucleic acids [ 12 ], and further studies should be able to define the specific functional groups on the nucleotide which form the hydrogen bonds. Alternatively, molecular dynamic simulations have been done to understand the interactions between polymers [ 108 , 109 , 110 ], including PEI and polylysine, with oligonucleotides. Similar studies could readily be applied to histidine-rich polymers and oligonucleotides.…”
Section: Challenges and Lingering Questionsmentioning
confidence: 99%
“…As previously discussed, NMR showed that histidines/imidazoles formed hydrogen bonds with nucleic acids [ 12 ], and further studies should be able to define the specific functional groups on the nucleotide which form the hydrogen bonds. Alternatively, molecular dynamic simulations have been done to understand the interactions between polymers [ 108 , 109 , 110 ], including PEI and polylysine, with oligonucleotides. Similar studies could readily be applied to histidine-rich polymers and oligonucleotides.…”
Section: Challenges and Lingering Questionsmentioning
confidence: 99%
“…For example, at full PLL protonation (which takes place at pH 5.4), the distance between macromolecules drops in a couple of nanoseconds (from roughly 40 Å to below 20 Å). At a smaller degree of protonation (50%, attainable at pH 7.4), the same distance between macromolecules is reached after roughly 30 s [110].…”
Section: Polymeric Non-viral Vectors For Gene Deliverymentioning
confidence: 97%
“…The intricate transport mechanism is not completely understood, and it is customarily narrowed down to a restrained collection of computational and experimental parameters [110]. The complexity of this puzzle is further enhanced by a wide variety of vector architectures and, thus, the ideal, both efficient (transport and safety) and easy-to-manufacture non-viral carrier cannot be fully described and designed.…”
Section: Polymeric Non-viral Vectors For Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, NIR as the excitation light of UCNPs is coincident with the biological transparency window; thus, greater tissue penetration depth and reduced background autofluorescence would be obtained ( Dong et al, 2017 ). Therefore, UCNPs have shown outstanding merits in in vitro fluorescence detection ( Tian et al, 2015 ), multimodal imaging in small animals, and drug carriers ( Vasiliu et al, 2017 ). In this work, we used UCNPs as the luminescence core and then coated them with a layer of cationic polymer, poly- D -lysine (PDL), as a gene carrier which has been frequently used due to its low gene transfection and the easy binding with nucleic acids ( Song et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%